Simplify (2×2 – 5x + 3) – (-x2 + 4x – 5) A) x2-x-2 3x²-3x-2 3x²-x+ 5 3x² – 9x=8

Question

Simplify
(2×2 – 5x + 3) – (-x2 + 4x – 5)
A)
x2-x-2
3x²-3x-2
3x²-x+ 5
3x² – 9x=8

in progress 0
Clara 2 weeks 2021-09-10T05:56:09+00:00 1 Answer 0

Answers ( )

    0
    2021-09-10T05:57:52+00:00

    Answer:

    3x² – 9x + 8

    Step-by-step explanation:

    (2x^2-5x+3)-(-x^2+4x-5)\\\\=2x^2-5x+3-(-x^2)-4x-(-5)\\\\=2x^2-5x+3+x^2-4x+5\qquad\text{combine like terms}\\\\=(2x^2+x^2)+(-5x-4x)+(3+5)\\\\=3x^2-9x+8

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )